Menuju Pemerintahan Digital Unggul: Tantangan dan Transformasi Indeks E-Government di Indonesia - Yazid, Ihsan Dailami; Karmila, Astineri Putri (Peneliti.net, 2024)
This research aims to assess the status of e-Government in Indonesia, identify the challenges in its implementation, and examine the evolution of Indonesia's digital government. The current dilemma facing the government involves harnessing technology to enhance public services and administrative functions. This study employs a combined approach of literature review and qualitative research. The data sources consist of secondary data, including findings from a Focus Group Discussion conducted by Litbang Kemendagri in May 2019 to pinpoint barriers to e-Government, an e-Government survey by the United Nations, and an E-Government Evaluation released by the Ministry of Administrative Reform and Bureaucratic Reform of Indonesia. The data is analyzed using descriptive analysis techniques.The findings indicate that Indonesia's progress in e-Government lags behind many other ASEAN countries. E-Government adoption varies among government institutions, with a noticeable disparity between central bodies and provincial/district governments. The hindrances to e-Government include (1) Insufficient regulations to promote and guide e-Government, (2) Limited data integration, (3) Disparities in ICT infrastructure availability across regions, (4) Inadequate ICT expertise, and (5) Bureaucratic culture and leadership issues. The e-Government Development Index (EGDI), which ranks 193 UN member countries, assesses performance in three dimensions: the Online Service Index (OSI), Telecommunication Infrastructure Index (TII), and Human Capital Index (HCI). Indonesia's EGDI ranking improved from 107 in 2018 to 88 in 2020. Several factors impede e-Government implementation, notably the slow adaptation of e-Government regulations and policies to the dynamic nature of ICT development and the public's digital service needs